Gambaran Konsep Diri Pada Pasien dengan Kanker Payudara Stadium III dan IV di Ruang Angsoka RSUP.Sanglah Denpasar - Fajar Lestari, Gusti Ayu Made Desi Anggryni; Muryani, Ni Made Sri; Rasdini, Gusti Ayu Ari; Sukanti, I Nengah (Akademi Keperawatan Kesdam IX/Udayana, 2017)
Background: Breast cancer (breast carsinoma) is a disruption in the normal mammary cell growth in which the abnormal cells arise from cells - normal cells, proliferate and infiltrate lymphoid tissue and blood vessels. One of the management of breast cancer (mammary carcinoma) is to perform surgery, and therefore a radical operative action resulting in loss of body parts has a psychological value and can not be avoided there is also a change - a change to the